UI/UX Design for Calligraphy Product Sales Application at Paris Store Using Design Thinking Method - M.Riyan Aidil Anwar; Heni Wulandari; Hermansyah (Cattleya Darmaya Fortuna, 2026)
Toko Paris is an UMKM engaged in the sale of Arabic calligraphy products and still runs a conventional sales system through physical stores. Therefore, a digital solution is needed that can improve service convenience and sales effectiveness. This study aims to design the user interface (UI) and user experience (UX) design on the Toko Paris mobile application by applying the Design Thinking method. This method is carried out through several main stages, namely empathize, define, ideate, prototype, and testing. The application display design was carried out using Figma software as a visualization medium for mobile design. Furthermore, the resulting prototype was evaluated using the System Usability Scale (SUS) method. The results of testing on 10 respondents by answering 10 questions and obtained a SUS score of 65 which is included in the adjective category Good and the acceptability level Marginal High. This application design is expected to be a digital solution that can support the increase in competitiveness of Toko Paris UMKM in facing the era of digital transformation.